“Eu e meu fole”: trajetórias formativas de seis sanfoneiros profissionais - Benigno, Rute Carolina da Cunha (2023)
The accordion is a very important instrument for the Northeastern and Brazilian musical culture, linked predominantly to aesthetic traditions and specific learning practices of popular music. The production of scientific knowledge in music is, little by little, covering this field and it is in this scenario that this research is located. This study seeks to understand the trajectory of musical formation of accordion players with a consolidated artistic career. Its specific objectives are: to analyze the situations and learning processes experienced by accordion players, as well as the relationships between such processes; describe techniques, styles, contexts and meanings present in their musical formation; and to identify the accordion players' conceptions about their own formative trajectory. For this research, a qualitative approach was adopted, using the History of Musical Life as methodology and, as the main data collection technique, the narrative interview. Six accordion players with consolidated and recognized professional performance in the Brazilian Northeast were interviewed. The narrative interview was complemented by a semi-structured interview based on the immanent contents of the first interview. The study is based on the Pierre Bourdieu’s sociology and on studies on Northeastern culture, learning in music and, specifically, in popular music. The analysis was also directed by studies about forró and accordion. The main learning practices analyzed were: familiarization, playing by ear, imitation, peer learning, formal studies, transposition of studies from other instruments and creation. As learning contexts, non-institutional ones predominate, with emphasis on the performance situation itself as a situation that promotes, in addition to musical learning, the development of professional practices of the accordion player. It is noticed that, along the trajectories, one learns not only to play the accordion, but to be an accordion player. Technical and aesthetic learning, the incorporation of culture(s) and professional practice are inseparable aspects in the trajectory of these subjects. The research contributes to understanding the learning practices of professional accordion players and popular musicians in general, and can add to broader reflections on popular culture and art.